(untitled) (World Bulletin of Social Sciences, 2023)
Today, trends in the use of information and communication technologies are an important factor in education. Also, the need for communication technologies in information is clear, and the article talks about the effective organization of procedures for preparing students of preschool education for professional creative activities based on information communication and digital technologies.